BOOK REVIEW: PIONEERS AND MILESTONES OF INDONESIAN GEOLOGY - Purba, Junida Rejeki; Darman, Herman (Berita Sedimentologi, 2025)
J.T. van Gorsel's four-volume series, "The Pioneers and Milestones of Indonesian Geology," provides a comprehensive exploration of the geological history of Indonesia. The books delve into the lives and contributions of 238 researchers, including geologists, paleontologists, and other scientists who have made significant advancements in understanding the region's complex geology.Through extensive research and analysis of historical documents, the author highlights the pioneering work of these individuals, many of whom were foreign-born and active during the Dutch colonial era. The books offer valuable insights into the challenges and rewards of conducting geological research in Indonesia, a region known for its diverse landscapes and complex geological processes.By preserving the legacy of these pioneers, Van Gorsel aims to inspire future generations of geoscientists and provide a solid foundation for ongoing research in Indonesian geology.